EXTENDING THE ANALYSIS OF KEY ISSUES IN INFORMATION TECHNOLOGY MANAGEMENT - Morgado, Eduardo M.; Reinhard, Nicolau; Watson, Richard T. (My University, 1995)
The key issues of Information Technology (IT) managers of Brazilian banking, a highly advanced industry, were assessed. The resulting priorities are comparable to those found in developed countries. As well as the usual key issues method of rating, two other methods were used: Q-sort and interpretive structured modeling (ISM). Respondents Q-sorted issues, and a factor analysis on these data identified four groups of banks with similar IT managerial issues. ISM provided a deeper understanding of the relationship among the top issues, and some previously lesser ranked issues ware recognized as more important. This study demonstrates how other approaches to assessing key issues provide additional insights into the key concerns facing IT managers.